A Novel Synthetic Method for N Doped TiO2 Nanoparticles Through Plasma-Assisted Electrolysis and Photocatalytic Activity in the Visible Region - Kim, Tae Hyung; Go, Gwang-Myeong; Cho, Hong-Baek; Song, Yoseb; Lee, Chan-Gi; Choa, Yong-Ho (Frontiers in Chemistry, 2018)
Nitrogen doped TiO2 (N-TiO2) nanoparticles were synthesized via a novel plasma enhanced electrolysis method using bulk titanium (Ti) as a source material and nitric acid as the nitrogen dopant. This method possesses remarkable merits with regard to the direct-metal synthesis of nanoparticles with its one-step process, eco-friendliness, and its ability to be mass produced. The nanoparticles were synthesized from bulk Ti metal and dipped in 5 – 15 mmol of a nitric acid electrolyte under the application of AC 500 V, the minimum range of voltage to generate plasma. By controlling the electrolyte concentration, the nanoparticle size distribution could be tuned between 12.1 nm and 24.7 nm using repulsion forces via variations in pH. The prepared N-TiO2 nanoparticles were calcined at between 100 – 300 oC to determine their photocatalytic efficiency within the visible-light region, which depended on their crystal structure and N doping content. Analysis showed that the temperature treatment yielded an anatase TiO2 crystalline structure when the N doping content was varied from 0.4 to 0.54 at.%. In particular, the 0.4 at.% N doped TiO2 catalyst exhibited the highest catalytic performance with quadruple efficiency compared to the P-25 standard TiO2 nanoparticles, which featured a 91% degradation of methyl orange organic dye within 300 min. This solid-liquid reaction based on plasma enhanced electrolysis could open new pathways with regard to high purity mass producible ceramic nanoparticles with advanced properties.